Uma perspectiva chinesa sobre os fatores culturais a serem considerados pelo brasileiro no processo de negociação com o chinês - Ponte, Yana (2007)
China emerges in the world as a potential economic leader and it is poised as the one of the strongest commercial partners of Brazil. China is already the third largest importer of Brazilian products and services and the prediction is to even increase that participation in the Brazilian export volume in the near future. As a consequence, there is a significant increase in commercial alliances between Brazilians and Chinese, which shows the need for the Brazilians to better understand the cultural differences when negotiating with the Chinese. The purpose of this research is to bring, from a Chinese point of view, the cultural difference in the negotiation process between Brazilians and Chinese. A better understanding of those differences will allow the Brazilians to adopt a better negotiation strategy with the Chinese in order to bring a better result. The research was developed by conducting 5 interviews with Chinese executives highly experienced in negotiation with the Brazilians. The results of this research show commons points indicated by the interviewers that have a direct impact on the negotiation process between Chinese and Brazilians.